Novela za 4-letno strokovno šolo - Žbogar, Alenka (Jezik in slovstvo, 2002)
The model for discussing Drago Jančar's short story Smrt pri Mariji Snežni (Death at Marija Snežna) from a 1985 collection of the same title may be optionally used in the final year vocational and technical schools (in dealing with contemporary Slovene narrative prose). It is adapted to these schools' populations in teaching aims, selection and classroom interpretation, which focuses on reception, interpretative reading and understanding with analysis. The model, which includes a work sheet and an evaluation sheet, establishes a link between literature and history classes and requires revision of the concepts 'short story', 'direct and indirect characterisation', and 'dramatic triangle'.
Keywords: Slovene literature; slovenska književnost; novela; pouk književnosti; metodika; Jančar, Drago: Smrt pri Mariji Snežni; srednje šole; matura